RAPT Industries, Inc. - Isaacs, Andrew M., (SAGE Knowledge. Cases., 2017)
The company name RAPT was an acronym for ReActive ion Plasma Technologies, a name that in spite of being cumbersome, accurately described the technology at the core of the new company. So far, RAPT had been a fantastic ride for its founders. Only a year old, the company had attracted the attention of some top industrial partners, raised enough cash for a year or more of operation, and to top it off, had won 1st place in the UC Berkeley Business Plan Competition, besting 65 competitors. Although the companys history up to this point had been a more or less linear path of iterative product development and market validation, RAPT was now facing some critical decisions with respect to its future direction, particularly with regard to funding, markets, and business models.